Performance Evaluation of Virtualization Tools in Multi-Threaded Applications - Sabolski, Ivan; Leventić, Hrvoje; Galić, Irena (International Journal of Electrical and Computer Engineering Systems, 2014)
In the last decade, virtualization technologies have become very popular. Virtualization enables a user to run multiple operating systems on the same computer concurrently, while providing a degree of isolation between OS instances. Even though virtualization is mostly used on servers, its popularity on desktop also rises, where it is mostly used in cross-platform development and execution of software available to other platforms. Since both of these use cases are performance intensive, the goal of this paper is to evaluate the performance of a couple of the most popular desktop virtualization tools on the market, i.e., VMWare Player and Oracle VirtualBox. Benchmarks used in this paper evaluate the performance of the tools in both CPU intensive and GPU intensive applications, with special emphasis placed on the performance of multi-threaded applications.